Ambient vibration testing of concrete dams - Bukenya, Patrick (Department of Civil Engineering, 2014)
In this thesis, seven techniques namely; rational fractional polynomial, complex exponential, frequency domain decomposition (FDD) based techniques which include; frequency domain decomposition (FDD), enhanced frequency domain decomposition (EFDD), curve fitting frequency domain decomposition (CFDD) and stochastic subspace identification (SSI) methods namely; unweighted principal component (UPC), principal component (PC) and canonical variant analysis (CVA)) have been applied to data from ambient vibration testing of two concrete dams namely; Roode Elsberg and Kouga dams.